LUCA BECCHETTI et al., The Vatican Secret Archives - Petrowski, Tyyne (Archivaria, 2010)
The Vatican Secret Archives. LUCA BECCHETTI et al. Foreword by Cardinal Raffaele Farina; translation by Monsignor James O’Brien; photography by Philippe Debeerst, Andrea Marini, and Enrico Ottaviani. Brussels: Paul Van den Heuvel – VdH Books, 2009. 252 p. ISBN 9789088810077.